THE PHENOMENON OF ONLINE PROSTITUTION THROUGH THE MI-CHAT APPLICATION IN INDRAMAYU DISTRICT - Natsir, Luthfi Faisal (PT. Antis International Publisher, 2024)
One of the social media applications that is misused as a tool for online prostitution transactions is Mi-chat or what the general public terms the